Sexual dysfunction in patients with schizophrenia – review of literature - Grzywa, Anna; Makara-Studzińska, Marta; Sosnowska, Katarzyna; Pakuła-Landman, Marta (Current Problems of Psychiatry, 2011)
Sexual dysfunctions are prevalent among patients with schizophrenia and may be related to both the psychopathology of disease and the pharmacotherapy. The negative symptoms of schizophrenia limit the capability for interpersonal and sexual relationships. Mechanisms for sexual dysfunction among patients with schizophrenia include medication-related effects, such as elevation of plasma prolactin levels, sedation owing to antihistaminergic effects, adrenergic effects and serotonergic blockade. The first-generation antipsychotics cause further deterioration of sexual functioning and consequently may decrease quality of life. Due to their fewer sexual side effects, the second-generation antipsychotics may provide an option for schizophrenia patients with sexual dysfunctions. Despite this, in scientific studies concerning several aspects of sexual self-perception, results revealed that schizophrenic patients, compared to healthy individuals, had significantly higher scores on the aspects of negative emotionality and sexual incompetence and significantly lower scores on the aspects of sexual satisfaction. Significantly higher scores of negative emotionality result from reduced interest in this sphere of life and the isolation of patients. No significant differences between acute and chronic schizophrenic patients regarding negative emotionality, perception of sexual incompetence and sexual satisfaction suggests that high negative emotionality, perception of sexual incompetence and low sexual satisfaction are not the results of long-lasting illness or lengthy taking of antipsychotics medication but phenotypic characteristics of schizophrenia. There is a significant influence of sexual problems on the decrease in quality of life and worse cooperation between patient and physician. Furthermore, most patients do not spontaneously report sexual dysfunction to their clinicians, because of the personal nature of sexual behavior. Thus, it is not possible to exclude such an essential aspect of life, and that is why careful interview and estimation of sexual functioning should be constant and indispensable component of psychiatric examination in both clinical and research settings.